2019
DOI: 10.1021/acs.jcim.8b00975
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Acetate Transport through the Acetate Channel SatP

Abstract: Acetate is a central metabolite that plays a key role in almost all organisms, and acetate channels are often essential for their survival. Recently solved structures of the acetate channel Succinate-Acetate Permease (SatP) provide an atomic view of its closed state. However, the open state of the channel, the key residue conformational changes that trigger the channel to open, and the free energy barrier of acetate transportation remain elusive. To address these questions, we performed microsecond time scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“… 400 Simulations of the structurally related SatP acetate channel showed that water hydrates all parts of the pore, including the central constriction site which forms an energetic barrier for acetate. 401 …”
Section: Aquaporins and Related Water And Polar Solute Poresmentioning
confidence: 99%
“… 400 Simulations of the structurally related SatP acetate channel showed that water hydrates all parts of the pore, including the central constriction site which forms an energetic barrier for acetate. 401 …”
Section: Aquaporins and Related Water And Polar Solute Poresmentioning
confidence: 99%
“…Branches that were not relevant were collapsed with the representative genus indicated. (18)(19)(20).…”
Section: Figmentioning
confidence: 99%
“…The Ato1 orthologues in Escherichia coli (ecSatP) and Citrobacter koseri (ckSatP) are so far the only members of the AceTr family whose structures are available (19,49). A hexameric UreI-like channel structure was reported for ecSatP (49); however, more recently, it was suggested that the closed state of the channel represents a relatively high energy barrier, 15 kcal/mol (20). The signature NPAPL GL(M/S) motif of the AceTr family, located at the beginning of the first TMS (Fig.…”
Section: Phylogenetic Evolution Of Ato Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…GPCRs at an atomic level and uncovering biomolecular mechanisms that are unattainable by experimental methods [26][27][28][29][30][31][32][33] . Integrating MD simulations with Markov state models (MSMs) [34][35][36] has proven successful in understanding the molecular switches in β2 adrenergic receptor, 37 elucidating ligand-driven conformational changes in CC chemokine receptor 2 38 , and revealing a cryptic pocket in dopamine D3 receptor 39 .…”
Section: Computational Methods Especially Molecular Dynamics (Md) Simentioning
confidence: 99%